(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Empathy is a complex multidimensional concept, which has an emotive, moral, cognitive and behavioural component. clinical empathy involves an ability to: (A) understand the patient’s situation, feelings, and Perspective; (B) communicate that understanding to patient accurately; (C) act on that understanding with the patient effectively way. The words like compassion, sympathy and empathy are commonly used terms unclearly, and there appear to be confusion about what these terms actually mean. compassion involves an active participation in another individual’s suffering rather than simply identifying with it; sympathy refers to the feelings we have in harmony with another person, it is emotional identification with the patient’s plight; and empathy refers to the understanding or reconstruction of another person’s emotions, it is involving passion and shared understanding. Empathy is major component of a satisfactory physician-Patient relationship, and there are many benefits to being an empathic physician, physician empathy has associated with satisfaction of physician and patient, fewer physician burnout, reduced malpractice complaints, decreased patient anxiety, better patient adherence to therapy, as well as improving the clinical outcomes. Empathy is learning able skill, and it could use vast collection of techniques for improving it among students of medical schools and practitioner.